(untitled) - Nguyễn, Hoàng Phương (Cần Thơ, 2020)
The study entitled “EFL Preservice Teachers’ Perceptions of the Requirements of Their Future Teaching Career and Context” is conducted with the aim of examining perceptions of the requirements of future teaching career and the English language teaching context from students who are studying English language education program. Data were collected from questionnaires administered to 119 students of English Education who are studying at a university in the Mekong Delta. The quantitative method is utilized in this study and questionnaire is the main instrument. The results indicated that participants strongly perceived the importance of these requirements within five domains in Competency Framework for preservice English language teacher by MOET: Knowledge of Subject, Knowledge of Language Teaching, Knowledge of Language Learners, Professional Values and Processes in Language Teaching and Connections to Practice and Context of Language Teaching. Furthermore, the similarities and differences in perceptions of freshmen and seniors participants were also found out. However, the study also reveals that freshmen participants perceived the requirements of their future teaching career and context stronger than seniors’. Therefore, the study findings suggest some pedagogical implications for preservice teachers of English Education as well as for English Language Education program, specifically in the Mekong delta and generally in Vietnam context.
Keywords: Anh ngữ,English language; Dạy và học,Study and teaching